Agricultural Risk Management: A Case Study On Rockmelon Farm At Sepang, Selangor, Malaysia - Rabihah Md Sum; Wira Abu Bakar (Malaysian Agricultural Research and Development Institute, 2024)
The aim of this study was to identify risks faced by farmers in agriculture projects and evaluate their risk management practices. A case study was conducted on a rock melon farm at Sepang, Selangor involving four farmers and two officers. Content analysis was used to analyse data collected from interview sessions. Risks were grouped into three criteria; risks created by farmers, internal operational risks and external operational risks. Risks by farmers were studied based on attitude, lack of knowledge/training, non-cooperation among farmers and non-adherence to SOPs. Risks by internal operation were mainly due to poor farm management, insufficient fund/capital, diverse farm activities and poor KPI. For risk from outside operation, the factors were changes in government policy. For agriculture production, risks were grouped into machine efficiency, pests and technology. For machine efficiency, the factors were immature technology and small firm size. For pest, the factors were pest attack and spread of disease. For technology, the factors were unsuitable technology for local farming, high cost and maintenance. For risk management practices, participants view risk management process as risk identification, risk evaluation, risk assessment and risk control. Risk management strategies to mitigate risks were product diversification, keeping record on farm activities, enhancing skills and knowledge in farm management, multitasking by farmers and having a comprehensive risk management guideline.